Mapping of Soil Stability based on Shear Wave Velocity Values (Vs30) Using the Multichannel Analysis Surface Wave (MASW) Method on Kalimantan Highway, Rawa Makmur Village, Bengkulu City - Putri, Aisyah Cindy Phylia; Refrizon, Refrizon; Hadi, Arif Ismul; Ansory, Andre Rahmat Al (JURNAL GEOCELEBES, 2025)
Kalimantan Highway in Bengkulu is a heavily traveled route and the main gateway to Bengkulu City from northern areas such as Arga Makmur and Ketahun sub-district, or Mukomuko regency also surrounding areas. Geological formations in the form of alluvium terraces (Qat) cause soil instability, often damaging the road surface. These include the formation of potholes and the occurrence of puddles during heavy rains. This research aims to determine the bearing capacity (stability) of the soil layer along Kalimantan Highway section in Rawa Makmur Village, Muara Bangkahulu District, and provide planning information through mapping. It is imperative to assess the condition of the soil layer. This research uses geophysical methods, specifically the Multichannel Analysis of Surface Wave (MASW) technique, using a MASW PASI 16S24-P digital seismograph to image subsurface soil conditions by analyzing shear wave velocity (Vs). A total of 20 data points were collected along the Kalimantan Highway section. The results of the Vs profile analysis were interpreted into soil classifications based on the criteria set out in SNI 1726:2019. The majority of the road sections were classified as SE (soft soil) and SD (medium soil), with some points designated as SC (hard soil/soft rock). This indicates that the geotechnical design for these road sections should consider supporting factors to maintain structural safety and stability.